Anticonvulsant and neurotoxicity evaluation of 5-(un)-substituted isatinimino derivatives - Pandeya S.N.; Sriram D.; Yogeeswari P.; Stables J.P. (My University, 2025)
Various Schiff bases were prepared by reacting 5-(un)-substituted isatin with some heterocyclic compounds, viz., N-[4-(4′chlorophenyl-thiazol-2-yl] semicarbazide, 3-amino-2-methylmercaptoquinazolin-4-one, 3-(4′-pyridyl)-4-amino-5-mercapto-4(H)-1,2,4-triazole and 4-(4′-chlorophenyl)-6-(4″-methylphenyl)-2-aminopyrimidine. The compounds were evaluated for anticonvulsant and neurotoxic properties. The compound 3-(3′,4′-dihydro-2′-methylmercapto-4′- oxoquinazolin-3′-yl) iminoisatin (3) emerged as the most active analogue showing anti-MES and anti-PTZ activities better than valproic acid. All the compounds showed lower neurotoxicity than phenytoin and carbamazepine.